PARENT-CHILD RELATIONSHIPS: COMPARATIVE LEGAL ANALYSIS OF RUSSIAN AND FOREIGN LEGISLATION - Gromozdina, Мария Владимировна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
Russian and foreign family legislation share many common provisions regarding the regulation of parent-child relationships. The essence of these provisions is that during childhood, legal norms assign obligations to parents and rights to children. However, adult children also bear certain obligations arising from their legal relationship with their parents, though these are not unconditional and require judicial assessment—such as in cases where children are required to pay alimony for the support of their parents. Based on this, it follows unequivocally that a minor child holds a determining position in the parent-child relationship system. Although parent-child relationships worldwide are regulated by largely similar norms in substance, there are also differences, some of which will be discussed further. It appears that the most legally complex issues involve child-rearing and disputes between parents, including in cases of divorce and separation, as well as determining the child’s opinion on matters affecting their interests, parental rights termination, and other related matters. For a comparative analysis of current family legislation in Russia and abroad, the author examined the legal acts of Kazakhstan, Belarus, Armenia, the United Kingdom, and other countries. As a result, the author reasonably concluded that the family laws of post-Soviet states share more similarities in their legal nature and regulation than with the norms of European legislation.